2014
DOI: 10.2478/geoca-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Dinosaur tracks from the Jurassic Shemshak Group in the Central Alborz Mountains (Northern Iran)

Abstract: Abstract:The Shemshak Group includes alternating layers of coal-bearing shale and siliciclastic sediments in the Baladeh area in the central Alborz Mountains of northern Iran. A diverse and abundant Jurassic dinosaur footprint assemblage is now recognized in the group, which is Toarcian to Bajocian in age in the northern Baladeh. This is the first report of a diverse dinosaur ichnoassemblage from Iran that includes the footprints of sauropods. These tracks can be assigned to three groups of trackmakers: therop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The siliciclastic Shemshak Group (Up per Tri as sic-Mid dle Ju rassic) is one of the most ex ten sive lithostratigraphic units of the Iran Plate, wide spread across the north ern Alborz and East Cen tral Iran of the Ira nian plate (Tabas and North of Kerman; Fürsich et al, 2009). Nu mer ous stud ies have doc u mented lithostratigraphic, sedimentological and palaeontological aspects of the Shem shak Group (e.g., Seyed-Emami et al, 2006;Fürsich et al, 2009;Shekarifard et al, 2009;Zanchi et al, 2009;Moosavirad et al, 2011Moosavirad et al, , 2012Abbassi and Madanipour, 2014;Salehi et al, 2017). These stud ies have shown that the Shemshak Group is com posed largely of siliciclastic rock, lo cally reach ing up to 4000 m in thick ness.…”
Section: Introductionmentioning
confidence: 99%
“…The siliciclastic Shemshak Group (Up per Tri as sic-Mid dle Ju rassic) is one of the most ex ten sive lithostratigraphic units of the Iran Plate, wide spread across the north ern Alborz and East Cen tral Iran of the Ira nian plate (Tabas and North of Kerman; Fürsich et al, 2009). Nu mer ous stud ies have doc u mented lithostratigraphic, sedimentological and palaeontological aspects of the Shem shak Group (e.g., Seyed-Emami et al, 2006;Fürsich et al, 2009;Shekarifard et al, 2009;Zanchi et al, 2009;Moosavirad et al, 2011Moosavirad et al, , 2012Abbassi and Madanipour, 2014;Salehi et al, 2017). These stud ies have shown that the Shemshak Group is com posed largely of siliciclastic rock, lo cally reach ing up to 4000 m in thick ness.…”
Section: Introductionmentioning
confidence: 99%
“…There is only a very sparse Mesozoic record of dinosaur tracks from Iran (Lapparent and Davoudzadeh 1972;Lapparent and Nowgol Sadat 1975;Ataabadi et al 2005;Abbassi 2006;Kellner et al 2012;Abbassi and Madanipour 2014;Abbassi et al 2015Abbassi et al , 2018. The bulk of the records is from the Lower and Middle Jurassic Ab-Haji Subgroup of the Shemshak Group of northern and Central Iran, and the uppermost Jurassic Ravar Formation of the Kerman area.…”
Section: Discussionmentioning
confidence: 99%
“…During a field survey in 2012, a dinosaur trampling site was discovered within the upper Campanian-Maastrichtian Farrokhi Formation and it was revisited and restudied in 2018. The aim of the current short note is the first report and scientific description of the site that supplements the sparse Mesozoic record of dinosaur tracksites from Iran (see Lapparent and Davoudzadeh 1972;Lapparent and Nowgol Sadat 1975;Ataabadi et al 2005;Abbassi 2006;Kellner et al 2012;Abbassi and Madanipour 2014;Abbassi et al 2015Abbassi et al , 2018, representing the youngest hitherto known occurrence. With our report, we also hope to stimulate further research on that topic in the area north of Khur where, in the future, additional and better-preserved tracks may emerge from the Farrokhi Formation.…”
Section: Introductionmentioning
confidence: 95%